Systemic delays in the initiation of antiretroviral therapy during pregnancy do not improve outcomes of HIV-positive mothers: a cohort study - Myer Landon; Zulliger Rose; Bekker Linda-Gail; Abrams Elaine (BMC, 2012)
Abstract Background Antiretroviral therapy (ART) initiation in eligible HIV-infected pregnant women is an important intervention to promote maternal and child health. Increasing the duration of ART received before delivery plays a major role in preventing vertical HIV transmission, but pregnant women across Africa experience significant delays in starting ART, partly due the perceived need to deliver ART counseling and patient education before ART initiation. We examined whether delaying ART to provide pre-ART counseling was associated with improved outcomes among HIV-infected women in Cape Town, South Africa. Methods We undertook a retrospective cohort study of 490 HIV-infected pregnant women referred to initiate treatment at an urban ART clinic. At this clinic all patients including pregnant women are screened by a clinician and then undergo three sessions of counseling and patient education prior to starting treatment, commonly introducing delays of 2-4 weeks before ART initiation. Data on viral suppression and retention in care after ART initiation were taken from routine clinic records. Results A total of 382 women initiated ART before delivery (78%); ART initiation before delivery was associated with earlier gestational age at presentation to the ART service (p < 0.001). The median delay between screening and ART initiation was 21 days (IQR, 14-29 days). Overall, 84.7%, 79.6% and 75.0% of women who were pregnant at the time of ART initiation were retained in care at 4, 8 and 12 months after ART initiation, respectively. Among those retained, 91% were virally suppressed at each follow-up visit. However the delay from screening to ART initiation was not associated with retention in care and/or viral suppression throughout the first year on ART in unadjusted or adjusted analyses. Conclusions A substantial proportion of eligible pregnant women referred for ART do not begin treatment before delivery in this setting. Among women who do initiate ART, delaying initiation for patient preparation is not associated with improved maternal outcomes. Given the need to maximize the duration of ART before delivery for prevention of mother-to-child HIV transmission, there is an urgent need for new strategies to help expedite ART initiation in eligible pregnant women.